PENGARUH SUBSTITUSI EKSTRAK KULIT BUAH NAGA MERAH TERHADAP KUALITAS ES KRIM - ELASTRI, APRINI; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2015)
This research is constituted by utilization of peel red dragon fruit at this time is stillnot optimal in food processing. Peel of red dragon fruit is containing betalain pigments aresoluble in water, and can be used natural dyes. The research purpose to analyze effect fromsubstitute extracting peel of red dragon fruit as much 13.5%, 32% and 50.5% of the icecream quality (color, aroma, texture, and flavor). The research type is experiment, methodeof this research using a completely randomized design with one factor that substitutingpeel red dragon fruit extract as much three times repetition. Data in use are primer dataobtained get from 30 panelists which give the answers from questionnaire (formatorganoleptic test). The data has been tabulated in tables and analysis variance (ANAVA).If diferent continued with Duncan test. The results of research showing there aresignificant between 0%, 13.5%, 32% and 50.5% to ice cream quality from peel extract ofred dragon fruit in color quality pink fanta Fh (442.17)> Ft (2.72), the quality of the milkaroma Fh (14:01)> Ft (2.72), texture quality is tender and creamy Fh (22:43)> Ft (2.72),but its not take effect of flavour quality is sweet Fh (2.62)> Ft (2.72). The highest resultsbe like panelists in substitute extracting peel of red dragon fruit as much 50.5% (X3). Canbe concluded that substitute peel extract of red dragon fruit as much 50.5% is the bestpercentage in use to colour quality and texture of ice cream.Keywords: peel Extract Red Dragon Fruit, Ice Cream, Quality